1998
DOI: 10.1007/s002620050522
|View full text |Cite
|
Sign up to set email alerts
|

Milky spots in the greater omentum are predominant sites of local tumour cell proliferation and accumulation in the peritoneal cavity

Abstract: The role that milky spots in the greater omentum play in tumour cell spread in the peritoneal cavity is presently not fully understood. To study whether intraperitoneally injected tumour cells appear preferentially in milky spots of the greater omentum and to study the changes in the greater omentum, and especially in the cell population of milky spots after tumour cell infiltration, the following study was performed. A detailed temporal sequences of changes in morphology and cellular composition in milky spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 12 publications
0
53
0
Order By: Relevance
“…Histologically, macrophages that accumulate around tumors are believed to be TAMs. Results from studies using mouse models have shown that secondary metastases are derived from newly generated milky spots that appear around the first metastatic spots (14). Therefore, the accumulation of foci of inflammatory cells would act as ''soil'' for the growth of cancer cells as ''seed'' (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, macrophages that accumulate around tumors are believed to be TAMs. Results from studies using mouse models have shown that secondary metastases are derived from newly generated milky spots that appear around the first metastatic spots (14). Therefore, the accumulation of foci of inflammatory cells would act as ''soil'' for the growth of cancer cells as ''seed'' (45).…”
Section: Discussionmentioning
confidence: 99%
“…Omentectomy is widely done to reduce the risk of recurrence and to improve survival (9,10). In addition, in a series of experimental studies, the omentum seemed to act as an initial implantation site for malignant cells (8,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This attachment has been observed for numerous cell lines in our study and is consistent with other investigations indicating that it occurs in diverse species including mice, rats, and humans. 6,7 The mechanisms responsible for the specific attachment remain to be determined. It is not clear whether the known filtering capacity of the immune aggregates 49 is involved in the attachment process or whether specific receptor/ligand pairs are required.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this apparent immune function, tumor cells can bind to the aggregates, suggesting that these sites may play an important role in peritoneal metastatic disease. 5,6,19,20 A primary tumor may shed a large number of metastatic tumor cells each day, yet only a few of these cells will actually develop into metastases. 21 Metastatic development is dependent on the acquisition of traits that promote survival by the tumor cells themselves as well as properties of the target tissue.…”
mentioning
confidence: 99%
“…Although myofibroblasts have been reported to derive from resident peritoneal fibroblasts, human peritoneal mesothelial cells (hPMCs) (16,17), bone marrow progenitor cells or the primary tumor itself (18,19), the origin of these myofibroblasts has not been clearly established. Also, during the initial stages of peritoneal (20)(21)(22)(23). Thus, the interactions between cancer cells derived from the primary tumor and submesothelium layer components such as myofibroblasts may be a key to peritoneal dissemination (24).…”
Section: Introductionmentioning
confidence: 99%